UPAYA PENINGKATAN KETRAMPILAN, KREATIVITAS MELALUI PELATIHAN PEMBUATAN PRODUK DAN PEMASARAN DIGITAL - Lestariningsih, Titin; Prabowo, Ivy Dian P; Taufiq, Ahmad; Mahmudi, Mahmudi; Kwantono, Hansel Timothy (Nindikayla Institute, 2023)
Facing the challenges of the Industry 4.0 era requires significant effort to remain competitive. To develop a resilient generation capable of tackling these challenges, skills and creativity are essential. The community service activities (abdimas) conducted by vocational higher education institutions are a form of academic community collaboration aimed at transferring knowledge and skills to the society. These abdimas activities are participated in by high school students during their vocational extracurricular sessions. The methods used in these abdimas include the provision of materials, training, and discussions. The materials and training focus on product creation and marketing. As a result of these abdimas, the high school students gain skills in creating marketplace seller accounts and managing food products. After participating in these abdimas, it is expected that the students will be able to start their own culinary businesses